An introduction to criminal justice - Harding, Jamie; Davies, Pamela; Mair, George (London : Sage, 2017)
The book is focused on criminal justice rather than criminology and the rationale for this book is to bring together a wealth of contemporary knowledge and thinking about matters concerning criminal justice in England and Wales.--from the Introduction.
Introduction / Pamela Davies, George Mair, Jamie Harding, Pamela Davies -- -- Part One : The criminal justice process in context / George Mair, Jamie Harding, Pamela Davies -- Criminal justice since 1945 : a brief history / George Mair -- Definitions and the counting of crime / Ian Mahoney -- Purposes of the criminal justice process / Joanne Clough -- Characteristics of offenders / Hannah Bows -- Diversity and the criminal justice process / Colin Webster -- Media representations of criminal justice / Ian Marsh -- Government, governance and criminal justice / Tim Newburn -- Researching criminal justice / Mike Hough -- Part Two : The criminal justice process / Jamie Harding, Pamela Davies, George Mair -- Community safety and crime prevention / Esther F.J.C. van Ginneken -- The police / Matt Jones and Kelly Stockdale -- Policing as part of a multi-agency approach / Tanya Wyatt and Mary Laing -- Prosecution and the alternatives / Alison Howey -- Criminal courts / Bankole Cole and Timi Osidipe -- Community sentences / George Mair -- Imprisonment / Charlotte Bilby -- Parole and release from prison / Harriet Pierpoint -- Youth justice / Tim Bateman -- Dealing with complaints and misconduct / Jamie Harding -- Supporting victims and witnesses / Ian R. Cook and Pamela Davies -- Part Three : Key issues in criminal justice / Pamela Davies, George Mair, Jamie Harding -- Does the criminal justice process work? / Mike Rowe -- Globalization and international criminal justice / Matthew Hall -- Criminal justice futures / George Mair, Jamie Harding, Pamela Davies.
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- England; Criminal procedure